An image cipher system based on networked chaotic map with parameter q. Issue 3 (25th November 2021) - Sun, Yu‐Jie; Zhang, Hao; Li, Zhen‐Yu; Wang, Xing‐Yuan; Wang, Chun‐Peng
Abstract: This paper models a networked coupling chaotic system with a fractional‐like local map based on network topology and fractional theory. The proposed model contains more system parameters and a more relaxed coupling relationship. The entropy analysis also shows that the proposed model is more sensitive to the changes in the coupling parameter. Based on this model, an effective image cipher system is designed using universal scrambling and diffusion based on DNA encoding. The proposed method utilizes the generated pseudo‐random signals from the networked chaotic map. The secret keys can be generated in parallel and the security is also improved due to the rise of complexity of the new chaotic map. Analysis and simulations confirm that the new chaotic map as well as the DNA encoding technology improves the effectiveness and robustness of the proposed encryption algorithm.